Ti-clinohumite in the Ciénaga skarn-type mineralogy, Sierra Nevada de Santa Marta Massif (Colombia): Occurrence and petrologic significance (2015)
This study reports the occurrence and petrologic significance of Ti-clinohumite for the first time in the Ciénaga skarn, Sierra Nevada de Santa Marta Massif. Ti-Clinohumite occurs as thin bands hosted in the Ciénaga Marbles of lower Cretaceous age, which consist of quartz-wollastonite-diopside-garnet-clinohumite marbles. We focus the attention on the occurrence of Ti-clinohumite-bearing domains, highlighting some interesting textures as well as the mineralogy and chemistry of the Ti-clinohumite. On the basis of its geologic situation, petrography, mineral composition and metamorphic history, we discuss the origin of Ti-clinohumite. ResumenEl estudio reporta la presencia y el significado petrológico de Ti-clinohumita por primera vez en mármoles del depósito de skarn de Ciénaga, Macizo Sierra Nevada de Santa Marta, de edad Cretácico inferior. La Ti-clinohumita ocurre como bandas delgadas en mármoles de cuarzo-wollastonita-diópsido-granateclinohumita. Centramos la atención en la ocurrencia de los dominios con Ti-clinohumita, destacando algunas de sus texturas interesantes, así como la mineralogía y la química de la Ti-clinohumita. Con base al contexto geológico, a las características petrográficas, a la composición mineral y a la historia metamórfica, se discute el origen de la Ti-clinohumita.